Cystic fibrosis program directors' attitudes toward sexual and reproductive health in young women with CF. Issue 1 (9th November 2015) - Kazmerski, Traci M.; Tuchman, Lisa K.; Borrero, Sonya; Weiner, Daniel; Pilewski, Joseph M.; Orenstein, David M.; Miller, Elizabeth
Summary: Introduction: Advancements in therapy have led to dramatic increases in the life expectancy of patients with cystic fibrosis (CF). As survival improves, young women with CF will have expectations for their sexual and reproductive health (SRH) futures similar to their counterparts without CF. As they face unique CF‐specific SRH concerns, they may rely on CF care providers for disease‐specific SRH care provision. The purpose of this study was to investigate the attitudes of CF providers toward female SRH and perceived barriers in the current CF care model. Materials and Methods: U.S. CF program directors (n = 16) participated in qualitative interviews investigating attitudes and barriers to female CF SRH care. Interviews were audio‐recorded, transcribed, and coded using a thematic analysis approach. Results: Participants (nine pediatric, five adult, and two combined) all agreed CF providers have a fundamental role in CF female SRH care. Most respondents named lack of time and patient and provider discomfort as significant barriers to effective SRH communication. Other reported barriers included: lack of training in SRH, family members in the room, low priority of SRH in setting of other CF issues, and lack of adequate rapport with patients. Discussion: This is the first study to assess the attitudes and experiences of CF care providers toward SRH discussion and care among female CF patients. Despite their perceived fundamental role in CF female SRH care, CF providers face significant barriers. Investment in provider training is needed to better address the complex SRH needs of young female patients.Pediatr Pulmonol. 2016;51:22–27. © 2015 Wiley Periodicals, Inc.